2021
DOI: 10.1186/s12903-021-01532-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychosocial distress and oral health status in patients with facial burns and mediation by oral health behaviour

Abstract: Background There is limited discussion on the influence of psychosocial factors on the oral health of patients with a facial burn injury. This report investigated the relationship between oral health and psychosocial distress in patients with facial burns and the role of oral health behaviour in mediating the relationship. Methods The data were part of a cross-sectional study that had systematically and randomly selected patients with > 10% tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This finding was statistically insignificant. This result was in line with the results of the previous studies where a greater risk of dental caries was related to irregular tooth brushing habits ( Ashour, Ashour & Basha, 2018 ; Chaudhary & Ahmad, 2021 ; Chaudhary, Ahmad & Bashir, 2019 ; Chaudhary, Ahmad & Sinor, 2021 ; Farooqi et al, 2015 ). Additionally, other oral hygiene habits like usage of dental floss and mouthwash/rinsing habits were found to be not significant among the study participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was statistically insignificant. This result was in line with the results of the previous studies where a greater risk of dental caries was related to irregular tooth brushing habits ( Ashour, Ashour & Basha, 2018 ; Chaudhary & Ahmad, 2021 ; Chaudhary, Ahmad & Bashir, 2019 ; Chaudhary, Ahmad & Sinor, 2021 ; Farooqi et al, 2015 ). Additionally, other oral hygiene habits like usage of dental floss and mouthwash/rinsing habits were found to be not significant among the study participants.…”
Section: Discussionsupporting
confidence: 92%
“…Another aspect of an inverse association of snacking with dental caries is the increased secretion of saliva due to more food consumption by obese people that could eventually reduce the incidence of caries owing to its protective effect. Additionally, studies have mentioned other factors such as poverty and low socioeconomic status that explain the relationship of being underweight and having more dental caries ( Chaudhary & Ahmad, 2021 ; Chaudhary, Ahmad & Bashir, 2019 ; Farsi et al, 2016 ; Kumar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study should be interpreted with caution due to the limitations mentioned earlier and in related publications [30,56]. A reliability study for the clinical measurements was not performed because the participants were not willing to return for re-assessment.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, more evidence is needed to reaffirm the observations. A recent study showed that psychosocial distress can affect oral health through oral health behaviour [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, WMSD pain was found more prevalent in female dentists and wrist pain occurs more often in oral surgeons compared to other dental professionals [ 13 ]. Some studies have correlated risk factors of WMSD among dentists with individual characteristics, physical load, and psychosocial factors [ 14 17 ]. However, most of the previous on WMSD among dental professionals were conducted in the western and developed nations, and only a few studies reported WMSD among dentists from the South Asia region.…”
Section: Introductionmentioning
confidence: 99%